A first glance at the coupled genitalia of the harvestmen Phalangium opilio (Eupnoi) - Werneck, Rachel M. (2016)
Harvestmen genital morphology has long been described mainly for taxonomic purposes, but genital coupling interactions remain largely unknown. Male genital functioning was generally inferred by artificial hydraulic expansion, since interactions between male genital parts (as well as their possible movements) were never seen. This is a huge information deficit for a better understanding of genital interactions in harvestmen, a group in which complex genital morphology suggests functions beyond gamete transfer/oviposition. Previously, we studied a Laniatorean species? coupled genitalia in some detail (unpublished data). Here we present the first observations for the suborder Eupnoi. Three pairs of Phalangium opilio in copula were freeze-fixed with liquid nitrogen. One pair was submitted to microCT scan and the others photographed, since they were clearly in early stages of penetration: beginning of penetration, and mouth rubbing. The images show interesting new facts, e.g. pre-penetration interaction, depth of penis penetration, stylus location in relation to seminal receptacles, penis and ovipositor contact regions. These results, even though preliminary, contribute to fill the gap in harvestmen functional genital morphology, and also provide consistent data for sexual selection hypotheses formulation.